"We Are Not Racists, We Are Nationalists": Communitarianism and Beitar Jerusalem. Issue 3 (1st December 2019) - Abutbul-Selinger, Guy
Abstract : This article explores the opposition expressed by fans of the Beitar Jerusalem football club to the presence of Arab players on their team. I suggest that instead of suspecting that fans' behavior originates in false consciousness, we suspend suspicion and reconstruct the meanings they bring to their actions. Narrative analysis of fan interviews reveals the communitarian logic underlying their points of view. By appropriating sacred spheres in Judaism that demarcate the boundaries of the Jewish community, and identifying them with Beitar as opposed to signifying Arab players as defiling Beitar, fans delineate boundaries between Jews and Arabs. Through the sanctification of Beitar, the fans define Jewish collective boundaries and thereby preserve their worldview and identity while maintaining a hierarchy that grants Jews advantages in Israel.